Exact and Approximate Models to Obtain Average Throughput of the FDDI MAC Protocol - Part II: Asymmetric Systems - LIM, K. S. (Institutional Knowledge at Singapore Management University, 1994)
The authors develop several simple iterative algorithms to obtain the approximate mean throughput of an asymmetric FDDI network. Although the methods presented are also applicable to symmetric networks (a symmetric network is just a special case of an asymmetric one), they provide only approximate estimates. Consequently, their practical use lie in estimating the mean throughput of asymmetric systems. The results obtained have been verified with detailed simulation runs from two different simulation models. They present a brief description of the model and a quick summary of the notations used. They also include the details of the analysis in two parts. The first part assumes a saturated synchronous stream while the second, unsaturated. A discussion comparing the results obtained by analysis and computer simulation is also presented